Potential contribution of gut microbiota and systemic inflammation on HIV vaccine effectiveness and vaccine design - Routy, Jean-Pierre (AIDS Res Ther, 2017)
The quest for an effective HIV-1 vaccine began as soon as the virus causing AIDS was identified. After several disappointing attempts, results of the Phase-III RV144 trial in Thailand were a beacon of hope for the field demonstrating correlation between protection and immunological markers. In order to optimize vaccine response, we underline results from yellow fever and hepatitis B vaccines, where protective responses were predicted by the pre-vaccination level of immune activation in healthy individuals. Such findings support the assessment and reduction of pre-vaccine immune activation in order to optimize vaccine response. Immune activation in healthy individuals can be influenced by age, presence of CMV infection, gut dysbiosis and microbial translocation. We speculate that the level of immune activation should therefore be assessed to better select participants in vaccine trials, and interventions to reduce inflammation should be used to increase protective HIV vaccine response.